Geophysical research on structure of partly eroded maar volcanoes: Miocene Hnojnice and Oligocene Rychnov volcanoes (northern Czech Republic) - Skacelova,Z.; Rapprich,V.; Valenta,J.; Hartvich,F.; Sramek,J.; Radon,M.; Gazdova,R.; Novakova,L.; Kolinsky,P.; Pecskay,Z. (Journal of Geosciences, 2010)
The internal structure of two partly eroded maar–diatreme volcanoes in the northern Czech Republic has been studied by combination of ground magnetometry, ground gravity measurements and multi-electrode resistivity profiling. Hnojnice and Rychnov maars were selected as maar–diatreme volcanoes described from surface geological survey and representing different country rock settings. The Hnojnice diatreme penetrates thick sequence of Upper Cretaceous marine sediments, whereas the Rychnov maar is situated within the crystalline rocks. This research improved the knowledge on geometry and dimensions of the studied diatremes.The basaltic feeder dyke of the Hnojnice maar has been discovered. The main dyke is located approximately in the axis of the maar. The dyke was detected within, and extending northwest of, the maar. According to the geophysical survey, several branches are associated with the main feeder dyke, one of them – funnel shaped ring dyke marks the outer limit of the diatreme. Other small branches (or larger basaltic clasts) are situated within the diatreme breccias.Basaltic dyke penetrating the Rychnov maar has been quarried in past. It was emplaced asymmetrically at the southwestern margin of the diatreme. According to the magnetometric survey, the dyke extends further to the northwest if compared with originally supposed extent. The dyke, and hence also the entire Rychnov maar, has been dated by the K–Ar method on bulk-rock to Late Oligocene (28.4 ± 1.3 Ma).
Keywords: Maar–diatreme volcano; ground magnetometry; ground gravity measurements; geoelectrical imaging; Bohemian Massif